APANG ARUU (SEBUAH KONTRADIKTIF PEMAKNAAN IDENTITAS TELINGA PANJANG PADA MASYARAKAT SUKU DAYAK KAYAAN MENDALAAM) - Maria Nyeti Nopitasari; Imma Fretisari; Ismunandar Ismunandar (Universitas Tanjungpura, 2020)
AbstractThe creation of dance “Apang Aruu” was inspired from Telinga Panjang tradition in Kayaan Mendalaam, Kapus Hulu regency. This tradition as identity of Apo Kayan ethnic such as Bahau, Kenyah and Kayaan. “Apang Aruu” was symbolized as the differences of human being and monkey, statue, gender and also the beauty symbol of dayaknesse women in Kayaan Mandalaam. As the time goes by, Telinga Panjang tradition gradually extinct because of belief, education and lifestyle in modern era. “Apang Aruu